European LeukemiaNet laboratory recommendations for the diagnosis and management of chronic myeloid leukemia - Cross, Nicholas C P; Ernst, Thomas; Branford, Susan; Cayuela, Jean-Michel; Deininger, Michael; Fabarius, Alice; Kim, Dennis Dong Hwan; Machova Polakova, Katerina; Radich, Jerald P; Hehlmann, Rüdiger; Hochhaus, Andreas; Apperley, Jane F; et al. (Leukemia, 2023)
From the laboratory perspective, effective management of patients with chronic myeloid leukemia (CML) requires accurate diagnosis, assessment of prognostic markers, sequential assessment of levels of residual disease and investigation of possible reasons for resistance, relapse or progression. Our scientific and clinical knowledge underpinning these requirements continues to evolve, as do laboratory methods and technologies. The European LeukemiaNet convened an expert panel to critically consider the current status of genetic laboratory approaches to help diagnose and manage CML patients. Our recommendations focus on current best practice and highlight the strengths and pitfalls of commonly used laboratory tests.
Keywords: recidiva; Recurrence; Protein Kinase Inhibitors; Humans; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; inhibitory proteinkinas; lidé; chronická myeloidní leukemie